Possibilidades da informática educacional na utilização de recursos tecnológicos digitais - Sant'Anna, Daniel Vieira (Editora Oficina Universitária, 2022)
Technology is present in human actions from the moment we begin to place instruments between us and the reality that surrounds us that expand our possibilities of action, whether in everyday tasks such as looking for roots, defending ourselves against other beings, building houses , on the hunt for survival. Today, these possibilities have expanded at a rate that cannot be measured. We are living the industry 4.0 revolution, what is the relationship with education, the subject of the work in question? The school is the institution that, for many, is the entry into the world of knowledge. We also know that the knowledge of information technology and digital communication - ICTD is today the key to enter the contemporary world, in this sense the work "Possibilities of educational informatics in the use of digital technological resources", presents us in a synthetic way and with actions that can support the uses of educational informatics. Reading the work will enhance and clarify many issues related to education and digital technological resources.